NEURAL NETWORK SIMULATION FOR STUDYING THE INFLUENCE OF DISPERSION PHASE CONDITIONS ON THE STABILITY OF SELENIUM COLLOIDAL SYSTEMS - M. A. Yasnaya; A. V. Blinov; A. A. Blinova; A. V. Kobina; A. A. Gvozdenko; D. G. Maglakelidze (Современная наука и инновации)
The article presents the results of determining the storage conditions for aqueous colloidal solutions of selenium stabilized with polyvinylpyrrolidone (PVP). The experimental data were processed using the Statistica Neural Networks v.4.0e software package. The analysis of the results showed that the optimal conditions under which colloidal solutions of selenium retain their biologically active properties for the longest time possible are: pH of the medium - weakly acidic or neutral; ionic strength of the solution - the minimum concentration of extraneous electrolytes; temperature - no higher than 30°С; holding time - only short-term effects, not causing irreversible changes in the properties of the colloidal system are permissible.